Penyelesaian Kerugian Investor Dari Praktik Insider Trading di Pasar Modal di Indonesia - Reyhan Rivelino; Lastuti Abubakar; Sudaryat Sudaryat (Jurnal USM Law Review)
The purpose of this research is to examine trading crimes insider are crimes that occur a lot in the Capital Market and are very difficult to prove in the process of handling and solving them so that in this case investors always get the biggest loss point. Law Number 8 of 1995 concerning Capital Markets as amended by Law Number 4 of 2023 concerning the Strengthening and Development of the Financial Sector explains the limitations and legal protection of investors related to Insider Trading practices, but this is considered insufficient to be able to protect investors optimally. This research is written using qualitative juridical writing techniques, namely describing data with theories to answer questions accompanied by legal interpretations so that conclusions can be drawn. The purpose of this study is to discuss how OJK as a supervisory institution in the capital market to handle and resolve Insider Trading practices and how repressive steps are taken after Insider Trading crimes occur so that the protection that investors should get will be realized.